Connecting In-Body Nano Communication with Body Area Networks: Challenges and Opportunities of the Internet of Nano Things - Dressler, Falko; Fischer, Stefan (Elsevier Nano Communication Networks)
Nano-communication is considered to become a major building block for many novel applications in the health care and fitness sector. Given the recent developments in the scope of nano machinery, coordination and control of these devices becomes the critical challenge to be solved. In-Body Nano-Communication based on either molecular, acoustic, or RF radio communication in the terahertz band supports the exchange of messages between these in-body devices. Yet, the control and communication with external units is not yet fully understood. In this paper, we investigate the challenges and opportunities of connecting Body Area Networks and other external gateways with in-body nano-devices, paving the road towards more scalable and efficient Internet of Nano Things (IoNT) systems. We derive a novel network architecture supporting the resulting requirements and, most importantly, investigate options for the simulation based performance evaluation of such novel concepts. Our study is concluded by a first look at the resulting security issues considering the high impact of potential misuse of the communication links.

Towards Communication Strategies for Platooning: Simulative and Experimental Evaluation - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Gerla, Mario; Lo Cigno, Renato; Dressler, Falko (IEEE Transactions on Vehicular Technology)
Platooning, the idea of cars autonomously following their leaders to form a road train, has huge potentials to improve traffic flow efficiency and, most importantly, road traffic safety. Wireless communication is a fundamental building block - it is needed to manage and to maintain the platoons. To keep the system stable, strict constraints in terms of update frequency and communication reliability must be met. We investigate different communication strategies by explicitly taking into account the requirements of the controller, exploiting synchronized communication slots as well as transmit power adaptation. As a baseline, we compared the proposed approaches to two state of the art adaptive beaconing protocols that have been designed for cooperative awareness applications, namely ETSI DCC and DynB. Our simulation models have been parameterized and validated by means of real-world experiments. Our results demonstrate that the combination of synchronized communication slots with transmit power adaptation is perfectly suited for cooperative driving applications, even in very crowded freeway scenarios.

Erleben Schulischer Wirklichkeit - Schulische Langeweile aus Sicht von Jugendlichen an Berufskollegs - Dirksmeier, V.; Gonsior, R.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kein Ende...vor dem Anfang einer weiteren Professionalisierung der Bildungsarbeit - Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Interference of surface plasmons and Smith-Purcell emission probed by angle-resolved cathodoluminescence spectroscopy - Yamamoto, Naoki; Javier García de Abajo, F.; Myroshnychenko, Viktor (Physical Review B)
We investigate the interplay between geometrical lattice resonances and surface plasmons mediating the emission of Smith-Purcell visible light via angle-resolved cathodoluminescence spectroscopy. We observe strong modulations in the dispersion curves of Smith-Purcell radiation (SPR) when they intersect the surface plasmons of silver gratings using a 200-kV transmission electron microscope. The decay of the plasmons away from the grating is directly probed by controlling the electron-beam position relative to the sample surface with nanometer precision. Our measurements are in excellent agreement with numerical simulations, clearly revealing the presence of characteristic Fano profiles resulting from the interference of the light continuum and the discrete plasmon states for each direction of emission. The intensity anomaly in the SPR emission pattern can be well explained from the geometrical consideration of the intersections between the dispersion planes of the SPR and surface plasmon polariton (SPP). A strong and directional SPR beam can be realized under the condition that the SPR dispersion plane comes in contact with the band edge of the SPP dispersion plane.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari

Pädagogische Hochschulentwicklung: Von der Programmatik zur Implementierung - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
Der Sammelband befasst sich mit einem umfassenden Ansatz zur Verbesserung der Qualität von Lehre und Studium. Mit dem Konzept der pädagogischen Hochschulentwicklung plädieren die AutorInnen dafür, bei der Umsetzung von Veränderungsprojekten die verschiedenen Ebenen der Hochschule zu verschränken. Zum Beispiel sollten Initiativen, die eine Lehrveranstaltung betreffen, idealerweise die (Aus )Wirkungen auf den Ebenen der Studienprogramme und der Organisation berücksichtigen und aktiv gestalten. Die einzelnen Beiträge stellen beispielhafte Initiativen aus unterschiedlichen Disziplinen und Hochschulformen dar und illustrieren, wie die genannten Ebenen in der praktischen Umsetzung verzahnt werden können.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari
Starting with this issue, the ZFHE will publish one English-speaking edition per year on a topic of international interest, in order to disseminate German-language research results beyond our borders and to encourage discussion in an international context. This first English-language edition focuses on the experiences and the academic socialization of first-year university students. The articles offer both diagnoses and differentiations in terms of different types of first-year students, as well as highlighting their experiences and development during their introduction to the academic environment and examining connections between their academic development and the existing educational environment.

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

How Do They Find Their Place? A Longitudinal Study of Management Students' Attitudes and Motivations During Their First Year at Business School - Jenert, Tobias; Brahm, Taiga
The first year of studying has been extensively researched applying different theoretical lenses to better understand the transition into Higher Education (HE). It is of particular interest to investigate how students deal with frictions between themselves as individuals and what they perceive to be dominant features of the first-year culture of their studies. To tackle this question, a qualitative longitudinal study was conducted. Based on a sociocultural understanding of attitudes and motivations, its aim was to closely follow a relatively small but highly diverse sample of students throughout their first year at a business school in order to develop an in-depth understanding of each individual’s motivational and attitudinal development.
Keywords: Enculturation; first-year students; beginning students; retention; drop-out

The crucial first year: Students’ motivation at a Swiss Business School--a longitudinal study - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Academy of Management Proceedings)
Despite students’ motivation being considered a strong predictor of performance, the development of motivation of business school students has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. This is surprising, as the transition from school to university is a crucial phase in the academic career and can be overwhelming for some students. The present study addresses this research gap and examines the development of economics and management students’ study motivation. The longitudinal study included four waves of data collected throughout the first year using quantitative surveys. Regarding students’ development over time, the analysis showed a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Zwischen" netten" Tools und" Überdidaktisierung": Neue Medien in der Hochschuldidaktik - Wagner, Dietrich; Jenert, Tobias
Auswertung einer Befragung unter Studierenden zu der Frage welche Elemente eine Lehrveranstaltung innovativ machen und welche Rolle die neuen Medien dabei spielen. Digitale Medien begegnen uns in der Hochschule immer wieder. Häufig handelt es sich um neue Werkzeuge oder Trends (Klicker, MOOCs, Web 2.0), die einerseits potenzialreich und spannend erscheinen, deren didaktische Verwertbarkeit sich aber nicht auf den ersten Blick erschließt. Oft folgt nach einer euphorischen Erprobung schnell die Ernüchterung, wenn festgestellt wird, dass sich durch die digitalen Technologien allein kein erhöhter Lernerfolg ergibt und auch die Studierenden keine nachhaltigen Motivationsschübe erfahren. Aus der Hochschuldidaktik hört man häufig und berechtigterweise kritische Stimmen, welche die Einbettung digitaler Medien in sorgfältig geplante didaktische Arrangements betonen. Es stellt sich die Frage, inwieweit damit die Kreativität und der Entdeckergeist von Lehrenden und Studierenden eingeschränkt werden. Wir wollen im Disq-Space der Frage nachgehen, wie die Hochschuldidaktik auf neue digitale Trends reagieren und dabei einen Mittelweg zwischen "kreativem Ausprobieren" und pädagogisch-didaktischer Rationalität einschlagen kann. Zunächst werden die Ergebnisse einer aktuellen Umfrage an der Universität St. Gallen zu den Vorstellungen Studierender zu innovativer Lehre vorgestellt. Nach einer Öffnung des Raums für gute sowie schlechte Erfahrungen und Bespiele von Seiten der Teilnehmenden soll diskutiert werden, welche personellen, didaktischen und organisatorischen Voraussetzungen erfüllt sein müssen, damit Digitalisierung die Kompetenzentwicklung der Studierenden unterstützt. Die Ergebnisse der Diskussionsrunde werden im Blog des Teams Hochschulentwicklung zur Verfügung gestellt. Es wird angestrebt, diese damit einer breiteren Öffentlichkeit zugänglich zu machen.
Keywords: Neue Medien; Hochschuldidaktik; Studierende; Innovation in der Lehre

On the iterative plug-in algorithm for estimating diurnal patterns of financial trade durations - Feng, Yuanhua; Forstinger, Sarah; Peitz, Christian (Journal of Statistical Computation and Simulation)

Forecasting financial market activity using a semiparametric fractionally integrated Log-ACD - Feng, Yuanhua; Zhou, Chen (International Journal of Forecasting)

Empirical Economic and Financial Research - Theory, Methods and Practice

Introduction - Beran, Jan; Feng, Yuanhua; Hebbel, Hartmut (Empirical Economic and Financial Research)

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Formula Apportionment or Separate Accounting? Tax-Induced Distortions of Multinationals' Locational Investment Decisions - Ortmann, Regina; Pummerer, Erich

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Hold or Sell? How Capital Gains Taxation Affects Holding Decisions - Hegemann, Annika; Kunoth, Angela; Rupp, Kristina; Sureth-Sloane, Caren

The Effect of Taxes on Corporate Financing Decision - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren

BI-Service-orientierte Leistungsverrechnung - Grytz, Raphael; Krohn-Grimberghe, Artus (Handbuch Business Intelligence. Potenziale, Strategien, Best Practices)

Fast Fuzzy Pattern Tree Learning for Classification - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Active zinc-blende III–nitride photonic structures on silicon - Sergent, Sylvain; Kako, Satoshi; Bürger, Matthias; Blumenthal, Sarah; Iwamoto, Satoshi; As, Donat Josef; Arakawa, Yasuhiko (Applied Physics Express)

Temperature dependence of the electron Landé g-factor in cubic GaN - Buß, J. H.; Schupp, T.; As, Donat Josef; Hägele, D.; Rudolph, J. (Journal of Applied Physics)

Strain dependent electron spin dynamics in bulk cubic GaN - Schaefer, A.; Buß, J. H.; Schupp, T.; Zado, A.; As, Donat Josef; Hägele, D.; Rudolph, J. (Journal of Applied Physics)

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)

How sales strategy translates into performance: The role of salesperson customer orientation and value-based selling - Terho, Harri; Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang (Industrial Marketing Management)

Heading for new shores: Do service and hybrid innovations outperform product innovations in industrial companies? - Eggert, Andreas; Thiesbrummel, Christoph; Deutscher, Christian (Industrial Marketing Management)

"...and they are really lying: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment" - Djawadi, Behnud Mir; Fahr, René (Journal of Economic Psychology)

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 3 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Wertbasiertes Verkaufen auf Industriegütermärkten - Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang; Terho, Harri (Handbuch Business-to-Business-Marketing)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Nuclear spin polarization in the electron spin-flip Raman scattering of singly charged (In,Ga)As/GaAs quantum dots - Debus, J.; Kudlacik, D.; Sapega, V. F.; Dunker, D.; Bohn, P.; Paßmann, F.; Braukmann, D.; Rautert, J.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transform-limited single photons from a single quantum dot - Kuhlmann, Andreas V.; Prechtel, Jonathan H.; Houel, Julien; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Nature Communications)

Influence of Post-Implantation Annealing Parameters on the Focused Ion Beam Directed Nucleation of InAs Quantum Dots - Mehta, M.; Reuter, Dirk; Kamruddin, M.; Tyagi, A. K.; Wieck, A. D. (Nano)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Extending the spectral range of CdSe/ZnSe quantum wells by strain engineering - Finke, A.; Ruth, M.; Scholz, S.; Ludwig, A.; Wieck, A. D.; Reuter, Dirk; Pawlis, A. (Physical Review B)

Skalieren von großen agilen Projekten mit verteilten Backlogs - Güldali, Baris; Fazal-Baqaie, Masud (OBJEKTspektrum (Online Themenspecials))

Agile Entwicklung mit On- und Offshore-Partnern – Methodenverbesserung in der Praxis - Fazal-Baqaie, Masud; Sauer, Stefan; Heuft, Torsten (WI-MAW-Rundbrief)

Towards a Framework for the Modular Construction of Situation-Specific Software Transformation Methods - Grieger, Marvin; Fazal-Baqaie, Masud (Softwaretechnik-Trends, Proceedings of the 17th Workshop Software-Reengineering (WSRE))